Handbook of Exoplanets 2017
DOI: 10.1007/978-3-319-30648-3_101-1
|View full text |Cite
|
Sign up to set email alerts
|

Exoplanet Atmosphere Measurements from Direct Imaging

Abstract: In the last decade, about a dozen giant exoplanets have been directly imaged in the IR as companions to young stars. With photometry and spectroscopy of these planets in hand from new extreme coronagraphic instruments such as SPHERE at VLT and GPI at Gemini, we are beginning to characterize and classify the atmospheres of these objects. Initially, it was assumed that young planets would be similar to field brown dwarfs, more massive objects that nonetheless share similar effective temperatures and compositions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 149 publications
(172 reference statements)
0
5
0
Order By: Relevance
“…Importantly, these observations, along with those of young, low gravity, isolated objects (e.g. Metchev et al, 2015;Gizis et al, 2015;Liu et al, 2016;Faherty et al, 2016;B. A. Biller et al, 2018;Vos et al, 2019Vos et al, , 2020, show that lower gravity objects tend to be more variable and possess redder near-infrared colors (higher J-K) compared to higher gravity objects of the same effective temperature ( Figure 5).…”
Section: Directly Imaged Planetsmentioning
confidence: 62%
See 2 more Smart Citations
“…Importantly, these observations, along with those of young, low gravity, isolated objects (e.g. Metchev et al, 2015;Gizis et al, 2015;Liu et al, 2016;Faherty et al, 2016;B. A. Biller et al, 2018;Vos et al, 2019Vos et al, , 2020, show that lower gravity objects tend to be more variable and possess redder near-infrared colors (higher J-K) compared to higher gravity objects of the same effective temperature ( Figure 5).…”
Section: Directly Imaged Planetsmentioning
confidence: 62%
“…Near-infrared spectroscopy of directly imaged companions has shown that, like isolated brown dwarfs, aerosols are common in their atmospheres and that the distribution of aerosols appears to be heterogeneous, with some objects exhibiting temporal variability in photometry and spectra (Marois et al, 2008;Currie et al, 2011;Skemer et al, 2012;Marley et al, 2012;Bonnefoy et al, 2013;Skemer et al, 2014;Ingraham et al, 2014;Macintosh et al, 2015;Zhou et al, 2016;Bonnefoy et al, 2016;Rajan et al, 2017;Samland et al, 2017;Delorme et al, 2017;Greenbaum et al, 2018;Müller et al, 2018;B. A. Biller & Bonnefoy, 2018;Manjavacas et al, 2019;Lew et al, 2020;Bowler et al, 2020;Zhou et al, 2020;J.…”
Section: Directly Imaged Planetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct imaging observations of exoplanets are a complementary technique to study planetary atmospheres, and, like secondary eclipse and phase curve measurements, probe deeper into the planetary atmospheres than tranmission spectroscopy. Such data can achieve higher S/N of interesting fea- tures [169,170]. As described in Section 3, Webb's instruments include coronagraphy modes at several wavelengths ranging from 1.7 to 22.75 microns.…”
Section: Direct Imagingmentioning
confidence: 99%
“…Adaptive optics (AO) imaging surveys determine crucial occurrence statistics for giant exoplanet populations with masses 1 M Jup at orbital separations >10 au and provide unique insight into their formation and migration histories (Bowler 2016;Meshkat et al 2017). Furthermore, resolving low-mass companions from their host stars reduces measurement noise allowing for indepth spectral characterization, which yields a wealth of information about the physical properties of their atmospheres (Biller & Bonnefoy 2017). AO observations also allow for the detailed mapping of scattered light from dust in circumstellar disks providing context for planet formation theories.…”
Section: Introductionmentioning
confidence: 99%